Fast finite-time consensus tracking for first-order multi-agent systems with unmodelled dynamics and disturbances - Sun, Chao (2015)
In this paper, we study fast finite-time consensus tracking problem for a class of first-order multi-agent systems with unmodelled dynamics and unknown disturbances. A continuous control law is proposed to guarantee fast finite-time consensus tracking of a desired signal despite of uncertainties and disturbances in the system dynamics. Sufficient conditions for finite-time consensus tracking are established by using Lyapunov analysis methods. A numerical example is provided to show the effectiveness of the proposed algorithm.